The broad autism phenotype in parents of individuals with autism: a systematic review of the literature - Lidia Prata Cruz; Walter Camargos-Junior; Fabio Lopes Rocha (Trends in Psychiatry and Psychotherapy, 2013)
The broad autism phenotype (BAP) is a milder manifestation of the defining symptoms of the syndrome in individuals without autism. This study conducted a systematic review of studies about behavioral characteristics of interpersonal relationships, communication and rigidity, as well as about three cognitive models, Theory of Mind, central coherence and executive function, in parents of individuals with autism. The indexed databases were LILACS, IBECS, Web of Science, and MEDLINE, and the studies retrieved were published between 1991 and March 2012. Parents of individuals with autism have more difficulties in interpersonal relationships and in pragmatic language use and have more rigidity traits. The inclusions of the cognitive theories in the group of BAP characteristics were inconclusive.